Baseline malarial and nutritional profile of children under seasonal malaria chemoprevention coverage in the health district of Nanoro, Burkina Faso - Paul Sondo; Toussaint Rouamba; Marc Christian Tahita; Karim Derra; Berenger Kabore; Yssimini Nadège Guillène Tibiri; Hyacinthe Abd-El Latif Faïçal Kabore; So-vii Franck Hien; Florence Ouedraogo; Adama Kazienga; Hamidou Ilboudo; Eli Rouamba; et al. (PLoS ONE, 2023)
Seasonal Malaria chemoprevention (SMC) is one of the large-scale life-saving malaria interventions initially recommended for the Sahel subregion, including Burkina Faso and recently extended to other parts of Africa. Initially, SMC was restricted to children 3 to 59 months old, but an extension to older children in some locations was recently recommended. Further characterization of SMC population profile beyond age criterion is necessary for understanding factors that could negatively impact the effectiveness of the intervention and to define complementary measures that could enhance its impact. Children were assessed through a cross-sectional survey during the first month of the 2020 SMC campaign (July-August 2020) as part of the SMC-NUT project in the health district of Nanoro. Parameters such as body temperature, weight, height, mid-upper arm circumference (MUAC) were assessed. In addition, blood sample was collected for malaria diagnosis by rapid diagnostic tests (RDT) and microscopy, and for haemoglobin measurement. A total of 1059 children were enrolled. RDT positivity rate (RPR) was 22.2%, while microscopy positivity rate (MPR) was 10.4%, with parasitaemia levels ranging from 40 to 70480/μL. RPR and MPR increased as patient age increased. Wasting was observed in 7.25% of children under SMC coverage while the prevalence of stunting and underweight was 48.79% and 23.38%, respectively. As the age of the children increased, an improvement in their nutritional status was observed. Finally, undernourished children had higher parasite densities than children with adequate nutritional status. In the health district of Nanoro, children who received Seasonal Malaria Chemoprevention (SMC) were mostly undernourished during the period of SMC delivery, suggesting the need for combining the SMC with synergistic interventions against malnutrition to achieve best impact.